Kuliner Etnik Binongko pada Tradisi Pisaba’a di Kelurahan Wali Kecamatan Binongko Kabupaten Wakatobi - Binarti Binarti; Wa Kuasa Baka; Samsul Samsul (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2022)
This study aims to identify the cuisine served and to understand the meaning contained in the cuisine tradition of Pisaba'a in the Binongko ethnic group. The method used in this research is field research, where data collection is done using observation, interview, and documentation techniques. The data obtained was analyzed descriptively using qualitative methods with Charles Sanders Pierce's semiotic theory. The results of the research showed that the cuisine in the Pisaba'a tradition consists of mandatory cuisine and additional cuisine. The cuisine in the Pisaba'a tradition has meanings about human life.